Sound pronunciation correction in patients after glossectomy. Сomparative prospective study - E. A. Krasavina; E. L. Choynzonov; D. E. Kulbakin; V. O. Tskhai; L. N. Balatskaya (Сибирский онкологический журнал)
The purpose of the study was to compare the effectiveness of correction of sound pronunciation in patients after glossectomy without reconstructive surgery and glossectomy with reconstructive surgery. Material and Methods. The study included 56 patients with histologically verified stage III –IV oral cavity and oropharyngeal cancer. All patients were divided into two groups: those undergoing reconstructive surgery after glossectomy and those not undergoing reconstructive surgery after glossectomy. Data on the dynamics of sound pronunciation correction were assessed during the rehabilitation period, as well as 6 and 12 months after completion of speech therapy. The parameters were scored from 0 to 4, where 0 indicated no speech sound disorders, and 4 indicated maximum disorders. Results. All patients showed absolute (4 points) speech sound disorders after surgery. Speech rehabilitation in patients, who underwent reconstructive surgery after glossectomy, resulted in a significant improvement in the pronunciation of posterior lingual sounds: [K], [G], [K’], [G’], whistling (lingual-dental) sounds: [S], [S’], [Z ], [Z’], front-lingual sounds: [T], [Т’], [D], [D’] and hissing sounds: [Sh, [Zh] (p<0.05). In patients, who underwent glossectomy without reconstructive surgery, a statistically significant improvement in sound pronunciation was observed only after correcting posterior lingual hard sounds: [K], [G] (p<0.05). Conclusion. The results obtained highlight the importance of reconstructive surgery after glossectomy to achieve better results of functional restoration and improve the quality of speech function of patients.